2010
DOI: 10.1029/2010jd014185
|View full text |Cite
|
Sign up to set email alerts
|

Validating the reported random errors of ACE‐FTS measurements

Abstract: [1] In order to validate the reported precision of space-based atmospheric composition measurements, validation studies often focus on measurements in the tropical stratosphere, where natural variability is weak. The scatter in tropical measurements can then be used as an upper limit on single-profile measurement precision. Here we introduce a method of quantifying the scatter of tropical measurements which aims to minimize the effects of short-term atmospheric variability while maintaining large enough sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…This method has been applied in several previous studies to satellite measurements to validate the reported precision. For example, Toohey et al [2010] use the short-term scatter in tropical Atmospheric Chemistry Experiment-Fourier Transform Spectrometer (ACE-FTS) measurements to validate the reported random error for several retrieved molecular concentration profiles. Piccolo and Dudhia [2007] compare the standard deviation of Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) retrievals at the intersections of ascending and descending legs of the orbit track to validate the reported precision of MIPAS Level 2 products, and uncertainties in Microwave Limb Sounder (MLS) ozone retrievals are characterized similarly by Froidevaux et al [2008].…”
Section: Osiris "Matched Pair" Measurementsmentioning
confidence: 87%
“…This method has been applied in several previous studies to satellite measurements to validate the reported precision. For example, Toohey et al [2010] use the short-term scatter in tropical Atmospheric Chemistry Experiment-Fourier Transform Spectrometer (ACE-FTS) measurements to validate the reported random error for several retrieved molecular concentration profiles. Piccolo and Dudhia [2007] compare the standard deviation of Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) retrievals at the intersections of ascending and descending legs of the orbit track to validate the reported precision of MIPAS Level 2 products, and uncertainties in Microwave Limb Sounder (MLS) ozone retrievals are characterized similarly by Froidevaux et al [2008].…”
Section: Osiris "Matched Pair" Measurementsmentioning
confidence: 87%
“…It should also be noted that in atmospheric science, the use of PDFs is not uncommon in tracer and validation studies. Lary and Lait (2006), in their introduction, give excellent examples of different types of tracer studies; and studies such as Migliorini et al (2004), Lary and Lait (2006), and Wu et al (2008) have demonstrated that PDFs can be used as a validation tool, where PDFs as measured by different atmospheric sounders are inter-compared rather than inter-comparing co-located measurements.…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of points, from 60°N to 60°S (c.f. Figure 1), the modifications made using Equation (2) has only a minimal effect and is within the measurement uncertainty calculated using the ACE-FTS error estimates (see Toohey et al, 2010, for details on ACE-FTS error estimation).…”
Section: Significancementioning
confidence: 99%